What's Wrong with Work? - Pettinger, Lynne (Book collections on Project MUSE., 2019)
Why does work matter? What's wrong with work? shows that how work is organised has wide implications beyond the lives of workers themselves. Recognising gender, race, class and global differences, the book looks at three kinds of increasingly important work - green work, IT work and the informal economy - within the context of present-day economic crises, anticipated environmental catastrophe and the false promises of technologisation. Accessible and engaging, the book refuses simple solutions and argues for collective responsibility in addressing the damages of work. --